The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1161/jaha.121.023251
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Cardiac Outcomes of Multisystem Inflammatory Syndrome in Children Associated With COVID‐19 Infections

Abstract: Background In multisystem inflammatory syndrome in children, there is paucity of longitudinal data on cardiac outcomes. We analyzed cardiac outcomes 3 to 4 months after initial presentation using echocardiography and cardiac magnetic resonance imaging. Methods and Results We included 60 controls and 60 cases of multisystem inflammatory syndrome in children. Conventional echocardiograms and deformation parameters were analyzed at 4 time points: (1) acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
96
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(106 citation statements)
references
References 35 publications
8
96
2
Order By: Relevance
“…Moreover, elevated troponin concentration, before the outbreak of the COVID-19 pandemic, was recognised as a poor prognostic marker in adult patients with acute coronary syndrome, as well as in children with acute fulminant myocarditis [ 26 ]. Contrarily, according to a retrospective by Matsubara et al, longitudinal cohort study troponin concentration seems to not be correlated with worse clinical implications in children with paediatric inflammatory multisystem syndrome temporary, associated with SARS-CoV-2 (PIMS-TS) [ 27 ]. In view of the above, and the supposed immune mechanism of PIMS-TS and COVID-19-vaccine-related myocarditis, the troponin level appears to not reflect the CMR findings in wither of the abovementioned groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated troponin concentration, before the outbreak of the COVID-19 pandemic, was recognised as a poor prognostic marker in adult patients with acute coronary syndrome, as well as in children with acute fulminant myocarditis [ 26 ]. Contrarily, according to a retrospective by Matsubara et al, longitudinal cohort study troponin concentration seems to not be correlated with worse clinical implications in children with paediatric inflammatory multisystem syndrome temporary, associated with SARS-CoV-2 (PIMS-TS) [ 27 ]. In view of the above, and the supposed immune mechanism of PIMS-TS and COVID-19-vaccine-related myocarditis, the troponin level appears to not reflect the CMR findings in wither of the abovementioned groups.…”
Section: Discussionmentioning
confidence: 99%
“…Orange-colored: estimates and 95%-CI for children with SARS-CoV-2 infection; blue-colored: estimates and confidence intervals for children without SARS-CoV-2 infection in the 6 controlled studies 29-34 .…”
Section: Resultsmentioning
confidence: 99%
“…Risk of misclassification bias due to ambiguous definition of infection status was low for 14 uncontrolled studies that identified patients based on RT-PCR tests during acute COVID-19 30,32,35-44,47-49 .Three controlled studies 29,31,32 had moderate risk of bias either because positive infection status was defined by serology, but the infection time point was unclear or because negative infection status was defined by RT-PCR, but previous infection could not be excluded. The other 3 controlled studies 30,33,34 had serious risk of bias because negative infection status was determined on the basis of having no documented COVID-19 diagnosis 30 or symptoms 33,34 regardless of laboratory virus detection. Risk of bias due to missing data was serious in 14 studies, because loss-to-follow-up was either>20% 29,31-34,37,39,40,42,43,48,49 or the information provided was unclear 35,38 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations